The Influence of Honesty, Ethical Communication, and Islamic Social Responsibility on Brand Equity - Candraningrat Candraningrat; Yuli Yanti Wulansari (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2025)
This study aims to examine the influence of Islamic values in marketing communication on brand equity, focusing on brand awareness and brand image as outcome variables. Islamic values in marketing communication are conceptualized through three dimensions: honesty and truthfulness, ethical marketing communication, and Islamic-based social responsibility. A quantitative research approach was employed using a survey method, with data collected from 250 Muslim consumers. The data were analyzed using Structural Equation Modeling (SEM) with AMOS to test the proposed relationships. The results reveal that honesty and truthfulness have a positive and significant effect on both brand awareness and brand image. Ethical marketing communication also significantly enhances brand awareness and brand image by fostering consumer trust and positive brand perceptions. Furthermore, Islamic-based social responsibility communication positively influences brand awareness and brand image, indicating that socially responsible messages aligned with Islamic principles strengthen brand equity. Overall, the findings confirm that integrating Islamic values into marketing communication serves as a strategic approach to building strong brand equity in Muslim-oriented markets. This study contributes to the Islamic marketing literature by providing empirical evidence on the role of value-based communication in enhancing brand awareness and brand image.